LA DESLOCALIZACIÓN DE EMPRESAS COMO FENÓMENO DE LA GLOBALIZACIÓN: SUS EFECTOS EN EL CAPITAL INTELECTUAL - López Salazar, Pedro (2006)
The globalization phenomena may be described as an increasingly close international integration of markets for goods, services and factors of production, labor and capital, guided by the evolution in information and telecommunications technology. For sure it is not a today’s created phenomena, once many of it’s characteristics already exist in the land’s discovery era, at sixteenth century. The intensity of globalization may be analyzed by commercial and financial relations, workers and labor flows, and technological aspects. It’s actuation range goes trough complex processes in technological, economics, politics and cultural dimensions. In this environment, in the course of the last years there has been a significant increasing in the difference among the assets of the companies registered in their accounting balance, and their true market value. This difference has led several specialists to identify the components of this additional value as intangible assets, or intellectual capital. However, one of the most recent processes in the globalization era is usually the move of companies, generally multinational, that transfer their work centers from developed countries to countries with smaller manpower costs, with a massive discharge of people that were working in them. Considering that substantial part of the intellectual capital is reflected in the knowledge, abilities, competences and inherent values of the individuals and groups that compose an organization, this work intends, after defining the processes of generation of the organizational knowledge through the collective learning of people or groups that compose the organization, verify existing intellectual capital measurement tools, and after analyzing the characteristics of the current move out of companies, to identify the components of the intellectual capital that get lost in this process, mainly that ones inherent to the persons. The main contribution of this work is, in fact, the proposal and description of those elements of the Intellectual Capital that may be affected as consequence of the phenomenon of companies move out, and the identification of the main factors inherent to this process in this new organizations challenge.